Birth order in small multihospital systems. - Luke, R D (1990)
The strategic behaviors of small multihospital systems have received little attention in the literature despite the fact that small systems are the predominant scale among multihospital systems. This study examines one important aspect of small-system strategic behaviors: the birth-order or evolutionary patterns of hospital acquisition. The evolutionary patterns of acquisition are compared across three strategic model types studied elsewhere: local market, investment, and historical. Using data obtained from a variety of sources, local market model systems are found, in the sequence of acquisition, to be significantly different from the other two model types in terms of relative distances of acquisitions from the initiating or parent hospital, the sizes of acquisition hospitals, the complexity of those hospitals, and the likelihood that the acquisitions are located in rural areas. Differences between parents and acquisitions are also significant, as hypothesized, for the market model system types, although they are not generally significant for the other two model types. The findings suggest that the market model represents an important strategic form that may have important implications for the restructuring of hospital markets.